Social media and democracy : the state of the field, prospects for reform - Persily, Nathaniel; Tucker, Joshua A. (Joshua Aaron), 1971- (Cambridge : Cambridge University Press, 2020)
Over the last five years, widespread concern about the effects of social media on democracy has led to an explosion in research from different disciplines and corners of academia. This book is the first of its kind to take stock of this emerging multi-disciplinary field by synthesizing what we know, identifying what we do not know and obstacles to future research, and charting a course for the future inquiry. Chapters by leading scholars cover major topics - from disinformation to hate speech to political advertising - and situate recent developments in the context of key policy questions. In addition, the book canvasses existing reform proposals in order to address widely perceived threats that social media poses to democracy. This title is also available as Open Access on Cambridge Core.
Introduction / Nathaniel Persily and Joshua A. Tucker -- Misinformation, disinformation, and online propaganda / Andrew M. Guess and Benjamin A. Lyons -- Social media, echo chambers, and political polarization / Pablo Barbera -- Online hate speech / Alexandra A. Siegel -- Bots and CompBots computational propaganda : automation for communication and controlutational propaganda / Samuel C. Woolley -- Online political advertising in the United States / Erika Franklin Fowler, Michael M. Franz, and Travis N. Ridout -- Democratic creative destruction? : the effect of a changing media landscape on democracy / Rasmus Kleis Nielsen and Richard Fletcher -- Misinformation and its correction / Chloe Wittenberg and Adam J. Berinsky -- Comparative media regulation in the US and Europe / Francis Fukuyama and Andrew Grotto -- Facts and where to find them: empirical research on Internet platforms and online speech / Daphne Keller and Paddy Leerssen -- Dealing with disinformation : evaluating the case for CDA 230 amendment / Tim Hwang -- Democratic transparency in the platform society / Robert Gorwa and Timothy Garton Ash -- Conclusion : the challenges and opportunities for social media research / Nathaniel Persily and Joshua A. Tucker.
Title from publisher's bibliographic system (viewed on 07 Sep 2020).
Keywords: Social media -- Political aspects; Online social networks -- Political aspects; Information society -- Political aspects; Information technology -- Political aspects; Democracy; Political participation -- Technological innovations